Kualitas Fisik dan Mikrobiologis Bakso Daging Sapi Pada Penyimpanan Suhu yang Berbeda (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
This study was conducted to determine the effect of different temperatures storage on the value of pH, water holding capacity, water activities, Total Plate Count and Escherichia coli contamination of beef meatballs during storage. The result showed that the highest pH value was in the freezer storage (5.83 ± 0.023). The highest value of water holding capacity was obtained at treatment dingingerator storage (23.33 ± 7.026 % water-free), while the results of the analysis of variance showed that effect of different temperature storage was not signiicant (P 0.05) than the meatballs in fresh condition. The analysis of variance showed that treatment of different temperature storage had no signiicant effect (P